2004
DOI: 10.1023/b:neon.0000027741.19213.99
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Mdm2, p53 and p16 in Patients with Astrocytomas

Abstract: Surgical cure of gliomas infiltrating into the brain is practically impossible and their clinical course is primarily determined by the biological behavior of the tumor cell. The purpose of this study was to analyze retrospectively prognostic input of p53, Mouse double minute-2 (Mdm2) and p16 in 103 uniformly treated patients with astrocytic tumors. The expression of these molecules was measured by immunohistochemical procedure. Prognostic evaluation was performed with the multivariate proportional hazards mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 32 publications
0
18
0
6
Order By: Relevance
“…Malignant glioma is the most common central nervous system (CNS) tumor, and mortality is extremely high [1,2]. Despite optimum treatment, median survival is only 12-15 months for patients with glioblastoma multiforme (GB), 2-3 years for patients with anaplastic astrocytoma (AA, WHO grade III), and 5-10 years for patients with diffuse astrocytoma (DA, WHO grade II) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Malignant glioma is the most common central nervous system (CNS) tumor, and mortality is extremely high [1,2]. Despite optimum treatment, median survival is only 12-15 months for patients with glioblastoma multiforme (GB), 2-3 years for patients with anaplastic astrocytoma (AA, WHO grade III), and 5-10 years for patients with diffuse astrocytoma (DA, WHO grade II) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found negative correlations between MDM2 tumor expression and prognosis in various cancers including breast, ovarian and brain [7-9]. Two studies have also noted a negative effect of MDM2 SNP309 G/G on survival of patients with metastatic gastric and renal cell cancer[10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, surgical cure, as the basic treatment of malignant gliomas, is rare, as it is practically impossible to resect effectively beyond the limits of a macroscopically visible tumour without drastically compromising neurologic function. As a result, gliomas have a poor prognosis [3,4]. In order to resolve this problem, many investigations have been performed and recent discoveries have shed light on the molecular events which deregulate the cell cycle in brain tumours.…”
Section: Introductionmentioning
confidence: 99%